2019
DOI: 10.1111/vsu.13207
|View full text |Cite
|
Sign up to set email alerts
|

Surgical enlargement of the nasomaxillary aperture and transnasal conchotomy of the ventral conchal sinus: Two surgical techniques to improve sinus drainage in horses

Abstract: Objective To evaluate 2 surgical techniques for establishing and/or improving paranasal sinus drainage in cadaver heads and horses with sinusitis and evaluate the feasibility of postoperative transnasal sinus endoscopy. Study design Ex vivo study (equine cadaver heads) and case series. Sample population Nine adult equine cadaver heads and 8 horses with recurrent sinusitis. Methods For the ex vivo study, the following procedures were performed on 9 cadaver heads: preoperative and postoperative computed tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…It is important to keep in mind that, in cases of secondary sinusitis, the treatment of the underlying cause is mandatory for long-term resolution of clinical sings [ 3 ]. Classical extra-nasal surgical techniques, including maxillary and frontal trephinations and bone flaps, have successfully been used to gain access to the sinus system and treat sinusitis [ 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] with or without sinuscopy via the externally created openings [ 3 , 8 , 10 , 14 , 15 , 16 , 17 ]. However, with improvements in the quality and size of endoscopes and instruments, transnasal endoscopically guided techniques have also been successfully used in the last 20 years [ 4 , 12 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to keep in mind that, in cases of secondary sinusitis, the treatment of the underlying cause is mandatory for long-term resolution of clinical sings [ 3 ]. Classical extra-nasal surgical techniques, including maxillary and frontal trephinations and bone flaps, have successfully been used to gain access to the sinus system and treat sinusitis [ 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] with or without sinuscopy via the externally created openings [ 3 , 8 , 10 , 14 , 15 , 16 , 17 ]. However, with improvements in the quality and size of endoscopes and instruments, transnasal endoscopically guided techniques have also been successfully used in the last 20 years [ 4 , 12 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Classical extra-nasal surgical techniques, including maxillary and frontal trephinations and bone flaps, have successfully been used to gain access to the sinus system and treat sinusitis [ 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] with or without sinuscopy via the externally created openings [ 3 , 8 , 10 , 14 , 15 , 16 , 17 ]. However, with improvements in the quality and size of endoscopes and instruments, transnasal endoscopically guided techniques have also been successfully used in the last 20 years [ 4 , 12 , 18 , 19 , 20 , 21 , 22 , 23 ]. These minimally invasive transnasal techniques can be divided into three groups.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment performed included surgical sinus access through a large fronto-nasal bone flap osteotomy and perforating the conchal wall for re-establishment of more permanent drainage to the nose proved to be successful for all cases without recurrence of fluid accumulation. However, a more minimally invasive approach, such as transendoscopic laser fenestration ( 20 , 21 ) or endoscopy-guided transnasal conchotomy ( 22 , 23 ), might be more sufficient to restore sino-nasal drainage in these cases. However, the obstructed nasal passages precluded such an approach.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the surgical procedure has been relatively blood-free, this procedure creates immediate and significant haemorrhage. To overcome this problem but maintain good post-operative drainage from infected sinuses, or to facilitate post-operative management, the balloon sinoplasty procedure was developed (Bell et al 2009); and more recently Bach et al (2019) reported on using a combination of electrocautery and sharp surgery to perform a transnasal conchotomy and surgical enlargement of the nasomaxillary aperture (SENMAP). Following these procedures, the packing can be passed through the widened nasomaxillary aperture into the middle and ventral meati and down the nostril.…”
Section: Introductionmentioning
confidence: 99%
“…2009); and more recently Bach et al . (2019) reported on using a combination of electrocautery and sharp surgery to perform a transnasal conchotomy and surgical enlargement of the nasomaxillary aperture (SENMAP). Following these procedures, the packing can be passed through the widened nasomaxillary aperture into the middle and ventral meati and down the nostril.…”
Section: Introductionmentioning
confidence: 99%